Performance analysis of U19 male and female setters in the Brazilian volleyball champion teams (Kinesiology, 2021)
The present study aims to analyse the associations between setting variables and gender (male and female). The study sample consisted of 711 setting actions made by the setters/starters of the champion teams from the Brazilian states of Minas Gerais (MG) and São Paulo (SP); 313 setting actions were observed for the male category and 398 for the female category. Statistical analysis showed that there were gender differences in the following variables: conditions of the setting, number of attackers available for the attack, set tempo, conditions after setting and the set’s area. This information is likely to be relevant for the training process of setting, for both males and females.Key words: performance, genders, volleyball, setting, training stages